IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT DAN PENGUJIAN KATALON PADA APLIKASI LAPORAN BARANG RUSAK - Ruhiyat, Yayat; Nurfalah, Ridan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
The management of State-Owned Assets (BMN) within the Secretariat General of the National Resilience Council faces challenges in recording and reporting damaged assets. The current manual process leads to delays, data inaccuracies, and hinders effective asset maintenance. This study aims to design and develop the Labarus (Laporan Barang Rusak) application as a digital solution to support faster and more accurate recording and monitoring of damaged BMN assets. The Rapid Application Development (RAD) method was used to accelerate the application development process through an iterative approach that allows for prototyping and immediate validation by users. Application testing was conducted using Katalon to ensure functional compliance with requirements and compatibility across various devices. The outcome of this research is a web-based application that enables users to report damaged goods online, track the status of repairs, and automatically generate damage and repair reports. This application reduce recording errors, speed up the repair process, and support the ongoing digital transformation in Setjen Wantannas. This research contributes by developing a web-based application called LABARUS (Laporan Barang Rusak) to replace the slow and error-prone manual processes, thereby enhancing the efficiency and accuracy of asset management in the Setjen Wantannas.